O uso das terapias de luz no manejo da radiodermite: consenso baseado na metodologia Delphi modificada - Lima, Talita Oliveira de (2024)
Cancer remains one of the most significant challenges in global public health, with radiotherapy (RT) being a cornerstone of oncological treatment. Radiodermatitis (RD), a skin lesion resulting from ionizing radiation, affects up to 90% of patients undergoing RT and may lead to severe complications. This study aimed to establish an evidence-based consensus on the optimal indications and therapeutic parameters for photobiomodulation (PBM) and photodynamic therapy (PDT) in RD management, focusing on safety, efficacy, and alignment with national and international guidelines. The methodology included two phases: an umbrella review of systematic reviews conducted in accordance with the PRISMA protocol, and a modified Delphi method involving two rounds of anonymous evaluations over six months. The analysis encompassed two consensus reports, four systematic reviews, and three meta-analyses, including over 400 patients with breast cancer and head-and-neck cancer. The findings suggest that PBM and PDT are promising interventions for managing RD, particularly in breast cancer patients, though variability in therapeutic parameters and evaluation methods persists. The consensus recommended initiating PBM early, from the onset of RT, to reduce grade 3 RD incidence, alleviate pain, accelerate tissue repair, and improve patients' quality of life. The RTOG scale was identified as a widely used and valuable tool for assessing lesion severity, although the need for more precise evaluation methods remains. However, no agreement was reached on specific patient subgroups most likely to benefit, despite evidence suggesting greater efficacy in cases involving extensive irradiated areas and higher radiation doses. Long-term safety and the effects of light-based therapies require further investigation. In conclusion, PBM and PDT are promising alternatives for RD management, but additional high-quality evidence is needed to establish standardized, reliable therapeutic protocols. Advancing the standardization of treatment parameters and developing tools to tailor therapies to individual patient profiles are critical to expanding the clinical applicability and benefits of these techniques. Such advancements are essential for integrating PBM and PDT into contemporary oncological care.